Desenvolvimento, caracterização e avaliação da atividade cicatrizante de nanopartículas contendo 17-β-estradiol e/ou óxido de zinco - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The aim of this paper was to obtain and characterize 17-β estradiol (E2) nanocapsules and zinc oxide (ZnO) nanospheres to evaluate the effect on cutaneous wound healing. The E2 nanoparticles was obtained using PCL polymer by pre-formed polymer precipitation method and the zinc oxide (ZnO) nanosphere by the co-precipitation method. The characterization was carried out using morphological and spectroscopic analysis. The analytical methods for quantifying E2 in nanocapsules have been validated as recommended by the International Conference on Harmonization. The stability of E2 formulations at 10°C, 25°C and 37°C was evaluated for 120 days. The animal assay was studied on oophorectomized Wistar rats by performing sirugical wounds and the animals were divided in 15 groups: CNO (non-oophorectomized control), CO (oophorectomized control), PCLN (nanocapsule without E2), EC and EN (0,06 and 0,12), ZnOC and ZnON (2,5 and 5,0) and ZnOC + EC and ZnON + EN (0,06 + 2,5 and 0,12 + 5,0). On days 7, 14 and 21, skin, uterus fragments and blood sample were collected and a histological analysis was performed using HE and picrosirius staining. The results showed adequate nanoparticles size, zeta potential and polydispersion for topical application on cutaneous wound. For quantification of E2, a simple and efficient method was developed using high performance liquid chromatography showing encapsulation efficiency above 99%. The morphology demonstrated a spherical and homogeneous nanoparticles. The FTIR spectra suggest that the E2 is dispersed in the oil phase of the nanocapsule. The samples showed adequated stability at differents temperatures with small pH variation and the maintenance of the size, zeta potential and polydispersion. For ZnO nanoparticles, the purity was performed using X-ray spectroscopy with energy dispersion showing zinc concentration about 76.82%. The FTIR spectra showed similar functional groups corresponding to the expected zinc oxide compound. The X-ray analysis showed smaller peaks at the defined positions, characteristic of zinc oxide crystallinity. The animal assay showed that there was no statistical difference in the wound retraction in all groups. The hematological analysis showed difference on the quantification of lymphocytes and neutrophils that are related to the effect described in the histological analysis of the skin. The oophorectomy surgery can delay the healing process. Treatment with ZnO and E2 may be able to modulate inflammatory phase mainly in treatment with nanoparticles. The association of treatment in the nanoparticulate form has favorable results in both the inflammatory phase and collagenesis. Histological changes in uterine tissue were greater in the group treated with EC 0.12 form. These results demonstrate that it was possible to obtain ZnO nanospheres and E2 nanocapsules with physical-chemical characteristics and with a potential effect on the healing process. This response was observed both in isolated treatments and in the association of nanoparticles. Thus, it was possible to develop a adequate alternative for the treatment of cutaneous wound in menoupausal women.
Keywords: Lesão cutânea; nanotecnologia; alteração hormonal; tratamento tópico; Cutaneous wound; nanotechnology; hormonal variation; topic treatment; CNPQ::CIENCIAS DA SAUDE::FARMACIA